2015
DOI: 10.1021/jp512378g
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy and Theoretical Calculations in the Conformational Analysis of 1-Methylpyrrolidin-2-one 3-Halo-derivatives

Abstract: This study reports the results of ab initio and density functional theory (DFT) electronic structure calculations as well as (3)J(HH) experimental and calculated coupling constant data obtained in the investigation of the conformational equilibrium of 3-halo-derivatives of 1-methylpyrrolidin-2-one. The five-membered ring assumes an envelope conformation owing to the plane of formation of the O═C-N-R bond, with C4 forming the "envelope lid". When the conformation changes, the "lid" alternates between positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…When the relative permittivity of the medium is increased, the pseudo-equatorial conformer becomes progressively more stable, mainly for fluorine and chlorine derivatives, while for bromine and iodine, electronic delocalization in the pseudo-axial conformer is so strong that the conformational equilibrium is practically insensitive to solvation. These statements are valid both for R = H and Me. , …”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…When the relative permittivity of the medium is increased, the pseudo-equatorial conformer becomes progressively more stable, mainly for fluorine and chlorine derivatives, while for bromine and iodine, electronic delocalization in the pseudo-axial conformer is so strong that the conformational equilibrium is practically insensitive to solvation. These statements are valid both for R = H and Me. , …”
Section: Introductionmentioning
confidence: 63%
“…Previous work of our research group showed that the 3-halosubstituted N -methyl-2-pyrrolidinones exist as an equilibrium between two conformations: one with the substituent in a pseudo-axial position ( p -ax) and the other, due to the pseudo-rotation of the five-membered ring, at the pseudo-equatorial position ( p -eq) (Figure ). Assuming that 3-chalcogenomethyl derivatives have the same conformational behavior, the stereochemical dependence of the spin–spin coupling constants can be used to gather information on the conformational preference of these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A general analysis of table 8 Good results for NMR data calculated with the DFT/B3LYP method have been also obtained, such as reported in works with 4', 7-dihydroxy-8-prenylflavan, 38 as well as 1-methylpyrrolidine-2-one-3-Halo-derivatives. 39 Here, the HF method used with basis set 6-31G** has also shown good results for NMR data prediction, with B classification.…”
Section: Nmr Spectramentioning
confidence: 81%